Atrophy of the Cholinergic Basal Forebrain can Detect Presynaptic Cholinergic Loss in Parkinson's Disease. Issue 5 (24th January 2023) - Ray, Nicola J.; Kanel, Prabesh; Bohnen, Nicolaas I.
Abstract : Objectives: Structural imaging of the cholinergic basal forebrain may provide a biomarker for cholinergic system integrity that can be used in motor and non‐motor outcome studies in Parkinson's disease. However, no prior studies have validated these structural metrics with cholinergic nerve terminal in vivo imaging in Parkinson's disease. Here, we correlate cholinergic basal forebrain morphometry with the topography of vesicular acetylcholine transporter in a large Parkinson's sample. Methods: [ 18 F]‐Fluoroethoxybenzovesamicol vesicular acetylcholine transporter positron emission tomography was carried out in 101 non‐demented people with Parkinson's (76.24% male, mean age 67.6 ± 7.72 years, disease duration 5.7 ± 4.4 years). Subregional cholinergic basal forebrain volumes were measured using magnetic resonance imaging morphometry. Relationships were assessed via volume‐of‐interest based correlation analysis. Results: Subregional volumes of the cholinergic basal forebrain predicted cholinergic nerve terminal loss, with most robust correlations occurring between the posterior cholinergic basal forebrain and temporofrontal, insula, cingulum, and hippocampal regions, and with modest correlations in parieto‐occipital regions. Hippocampal correlations were not limited to the cholinergic basal forebrain subregion Ch1‐2. Correlations were also observed in the striatum, thalamus, and brainstem. Interpretation: Cholinergic basal forebrain morphometry is a robust predictor of regional cerebral vesicular acetylcholine transporter bindings, especially in the anterior brain. The relative lack of correlation between parieto‐occipital binding and basal forebrain volumes may reflect the presence of more diffuse synaptopathy in the posterior cortex due to etiologies that extend well beyond the cholinergic system. ANN NEUROL 2023;93:991–998